Meningkatkan Pendidikan Karakter Gotong Royong Siswa SD dengan Pembiasaan PenerapanTri Hita Karana - Iwan Usma Wardani; I Made Sutajaya; I Wayan Suja (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2023)
There are still many students who do not picket each other in class together. The students do not yet understand the meaning of the character value of mutual cooperation. The aim of this research is to improve the character of mutual cooperation through the habit of Tri Hita Karana. This research is classroom action research. The subjects in this research were 28 class IV students. This research was carried out using 2 cycles, each cycle consisting of four stages, namely: (1) Action Planning, (2) Action Implementation (3) Observation (4) Reflection. In this research, the data collection method used is the non-test method. And the data collection techniques in this research are observation and documentation techniques. Meanwhile, the data analysis techniques used in this research are qualitative and quantitative analysis techniques. In this research, researchers used several aspects of measuring the character of mutual cooperation which are guided by the Tri Hita Kirana, namely the concept of pawongan which is then explained through several indicators. The results of the implementation of actions in cycle I and implementation of cycle II showed that the average value of student character results in cycle I was 70% which was in the good category and the average value of student character results in cycle II was 85% which was in the very good category. . Based on this, it can be concluded that through Tri Hita Karana habituation, the character of mutual cooperation can improve and become a habit if given treatment and action repeatedly.